VD_FINDINFO Décision / 2012 / 133 vom 12. Juli 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL, PRÉVENU, AVOCAT, HONORAIRES | 395 let. b CPP (CH), 429 al. 1 let. a CPP (CH)